The Effectiveness of Peer Tutoring in Arabic Language Learning at Higher Education Institutions - Aminulloh, Lutfi; Al Faruq, Umar; A. Noer, Maulidia (UIN Maulana Malik Ibrahim Malang, 2025)
AbstractThis study investigates the effectiveness of peer tutoring in Arabic language acquisition at Maulana Malik Ibrahim State Islamic University in Malang. The aim is to explore how peer tutoring influences students' speaking proficiency, comprehension, and overall engagement compared to traditional instructor-led methods. Peer tutoring fosters a collaborative learning environment, promotes active participation, reduces language anxiety, and enhances motivation.A qualitative research approach was employed, using interviews, classroom observations, and reflective journals to gather data from advanced students acting as peer tutors and lower-level students as tutees. The study examined the interactions between these two groups, focusing on their impact on language proficiency and emotional engagement.The findings reveal that peer tutoring significantly improves speaking and comprehension skills, increases confidence in language use, and deepens understanding of grammar and vocabulary. Peer tutors also gained improvements in their own language skills, pedagogical techniques, and confidence. The supportive and non-intimidating environment reduced language anxiety, fostering higher student engagement. Peer feedback and collaborative learning were essential to improving language proficiency.This study confirms the pedagogical value of peer tutoring in Arabic language programs, suggesting its integration into curricula to improve learning outcomes and engagement. Future research could investigate long-term impacts and explore its effectiveness in diverse educational contexts.Keywords: Peer tutoring; Arabic language acquisition; student engagement; language proficiency; language anxiety; collaborative learning; peer feedback